Innovation objectives as determinants of organizational innovations. Issue 2 (3rd April 2017) - Meroño-Cerdán, Angel L.; López-Nicolás, Carolina
Abstract: This study analyzes the adoption of organizational innovations focusing on their drivers or objectives pursued. Complementarities of objectives and organizational innovations are considered together with a sectoral approach to evaluate differences between manufacturing and service industries. Based on the Community Innovation Survey (CIS), a canonical analysis is performed to allow the study of interrelationships among sets of multiple dependent variables (organizational innovations) and multiple predictor variables (objectives). Improving innovations skills is the most relevant objective in adopting any organizational innovation. Two objectives are closely related to innovations in workplace organization, namely reducing response time and cost (efficiency drivers). New business processes and external relations are more affected by desires to improve innovation skills and quality (intangible drivers). The results reveal similar behavior in manufacturing and service industries supporting the synthesis approach. Logit regressions confirm these findings.